CSR PERUSAHAAN DOMESTIK: IMPLEMENTASI, HAMBATAN, DAN SOLUSI (STUDI PADA PERUSAHAAN DOMESTIK DI JAWA TIMUR) - Siswati, Endang; Rosyafah, Siti (Unitri Press, 2023)
The aim of this research is to find out how corporate social responsibility is implemented in domestic companies and what are the obstacles to its implementation and what solutions to solve them. This research uses a qualitative approach using domestic companies in East Java as research objects. Data collection techniques were carried out using survey interviews and observations. After data triangulation was carried out, data analysis was carried out including data reduction, data presentation, and drawing conclusions. The research results found that the implementation of CSR for domestic companies in East Java includes, among other things, socialization, training, reducing environmental impacts, providing assistive devices for the disabled, free basic necessities and free cataract surgery. Obstacles in implementing CSR programs include obstacles from internal to the company, namely limited resources, while external to the organization, namely from consumers or environmental readiness. Solutions that can be implemented include CSR outreach activities and training. Conclusion: CSR in East Java is not only implemented by large companies but also domestic companies, the programs carried out are located around the company's environment. Obstacles from stakeholders are still found, both internal and external, which can be overcome by providing outreach and training.